Reliability of Metal 3D Printing with Respect to the Marginal Fit of Fixed Dental Prostheses: A Systematic Review and Meta-Analysis - Bae, Soohyun (Materials (Basel), 2020)
Three-dimensional (3D) printing technologies have been widely used to manufacture crowns and frameworks for fixed dental prostheses. This systematic review and meta-analysis aimed to assess the reliability of the marginal fit of 3D-printed cobalt-chromium-based fixed dental prostheses in comparison to conventional casting methods. Articles published until 25 June 2020, reporting the marginal fit of fixed prostheses fabricated with metal 3D printing, were searched using electronic literature databases. After the screening and quality assessment, 21 eligible peer-reviewed articles were selected. Meta-analysis revealed that the marginal gap of the prostheses manufactured using 3D printing was significantly smaller compared to that manufactured using casting methods (standard mean difference (95% CI): −0.92 (−1.45, −0.38); Z = −3.37; p = 0.0008). The estimated difference between the single and multi-unit types did not differ significantly (p = 0.3573). In the subgroup analysis for the measurement methods, the tendency of marginal discrepancy between the 3D printing and casting groups was significantly different between articles that used direct observation and those that used the silicone replica technique (p < 0.001). Metal 3D printing technologies appear reliable as an alternative to casting methods in terms of the fit of the fixed dental prostheses. In order to analyze the factors influencing manufacturing and confirm the results of this review, further controlled laboratory and clinical studies are required.